Pengaruh Harga Dan Kualitas Pelayanan Pada Kepuasan Dan Loyalitas Pengguna Kereta Api - Rachman, Natriya Faisal; Istiantara, Dedik Tri (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2017)
The quality of railroad service users in accordance with customer expectations can increase the tendency of customers to make repeat purchases, provide recommendations to others about their beneficial experiences, while customer loyalty is related to the possibility of returning customers, making business references, giving strong words, and offering references and publicity about services on the train. This study is a cross-sectional study where testing is based on data that occurs at one point in time, so that the model built is not designed to capture changes that occur due to time shift. The analysis in this study uses the statistical method of the Structural Equation Model (SEM). From the results of this study it can be concluded that the price, service quality, and customer satisfaction variables influence consumer attitudes towards loyalty applied to the Argowilis Train. This gives understanding for the Argowilis Train to see prices, improve service quality, and increase customer satisfaction.